Green synthesis and characterization of silver nanoparticles using Tualang honey and evaluation of their antioxidant activities. - Hasim, Hidani; Visweswara Rao, Pasupuleti Visweswara; Sekhar, A C; Muthuraju, Sangu; Asari, Mohd Asnizam; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Vietnam Academy of Science and Technology, 2020)
Natural products are widely used in the synthesis of various types of metallic nanoparticles including silver nanoparticles. Tualang honey is one of the potential natural products which is rich in polyphenols and antioxidant capacity. This study aims to synthesise and characterise the silver nanoparticles by using Tualang honey through green method and evaluate their antioxidant activities. The formation of silver nanoparticles was examined by visual observation and further confirmed by UV-Visible spectrophotometer. The characterisation of silver nanoparticles was determined by using x-ray diffraction, fourier transform infrared spectroscopy, field emission scanning electron microscopy and transmission electron microscopy analysis. The in vitro antioxidant activity of silver nanoparticles was evaluated by 1,1-diphenyl-2-picrul hydrazyl and ferric reducing antioxidant power assays. The synthesis was confirmed physically through the colour changes from light brown to dark brown which indicates the reduction of silver ion to silver nanoparticles. UV-Visible spectrum results showed the highest absorbance peak at 410 nm. X-ray diffraction results showed that the face-centred cubic crystalline shaped nanoparticles were formed. Fourier transform infrared spectroscopy results revealed the available functional groups that act as capping and stabilising agents for the silver nanoparticles. Field emission scanning electron microscopy analysis exhibited the spherical shape and transmission electron microscopy confirmed the size range of silver nanoparticles of 22 nm. The silver nanoparticles exhibited remarkable antioxidant activity with 1,1-diphenyl-2-picrul hydrazyl and reducing antioxidant power values of 95.54±0.96 (%) and 1032.30±102.76 μM Fe(II), respectively. In conclusion, the silver nanoparticles synthesised by green method can be a potential source for the biomedical applications based on the beneficial properties of the Tualang honey.